Regeneración del páncreas endócrino inducido por oligonucleótico IMT504 - Bianchi, Stefanía (2019)
Type 1 Diabetes Mellitus (DM1) is a disease caused by a progressive, autoimmune destruction of \ncells, which leads to a deficiency in the production and secretion of insulin. Unfortunately, patients\nwith DM1 lack the opportunity to change their blood glucose levels by doing exercise, eating a\nhealthy diet, or taking oral hypoglycemic drugs. So far, the usual and safe therapy is the daily,\nrepeated various times a day, administration of exogenous insulin.\nEven taking into account all the clinical advances in its way of administration and its formulations,\ninsulin treatment is a palliative therapy, which does not satisfactorily prevent long-term degenerative\ncomplications. Therefore, it is essential to find novel therapies that cure this pathology.\nHere we propose: IMT504, a synthetic oligodeoxynucleotide (ODN) with a defined sequence, as a\npossible alternative therapy, based on its effects observedin immune-compromised diabetic animals.\nIn this work, we have demonstrated that IMT504 improved glycemic metabolism and restored\nLangerhans islets in their morphology, quantity and beta cells content. Regarding the autoimmune\nattack, we observed that IMT504 exerts its known immunomodulatory effect in these models\nbydecreasing the islet leukocyte infiltration.\nConsidering this, furtherpreclinical and clinical studies are necessary to assess the efficacy of the\nIMT504 in autoimmune diabetes, in addition to determining its precise mechanism of action.